Burdens of Proposing: On the Burden of Proof in Deliberation Dialogues - Godden, David; Wells, Simon (Informal Logic)

(untitled) (Informal Logic, 2022)
This paper considers the probative burdens of proposing action or policy options in deliberation dialogues. Do proposers bear a burden of proof? Building on pioneering work by Douglas Walton (2010), and following on a growing literature within computer science, the prevailing answer seems to be “No.” Instead, only recommenders—agents who put forward an option as the one to be taken—bear a burden of proof. Against this view, we contend that proposers have burdens of proof with respect to their proposals. Specifically, we argue that, while recommenders that Φ bear a burden of proof to show that □Φ (We should / ought to / must Φ), proposers that Φ have a burden of proof to show that ◇Φ (We may / can Φ). A burden of proposing may be defined as , which reads: Those who propose that we might Φ are obliged, if called upon, to show that Φ is possible in any of four ways which we call worldly, deontic, instrumental, and practical. So understood, burdens of proposing satisfy the standard formal definition of burden of proof.